Screening for PPAR Non-Agonist Ligands Followed by Characterization of a Hit, AM-879, with Additional No-Adipogenic and cdk5-Mediated Phosphorylation Inhibition Properties - Ribeiro Filho, Helder Veras; Bernardi Videira, Natália; Bridi, Aline Villanova; Tittanegro, Thais Helena; Helena Batista, Fernanda Aparecida; de Carvalho Pereira, José Geraldo; de Oliveira, Paulo Sérgio Lopes; Bajgelman, Marcio Chaim; Le Maire, Albane; Figueira, Ana Carolina Migliorini (Frontiers in Endocrinology, 2018)
Peroxisome proliferator-activated receptor gamma (PPARγ) is a member of a nuclear receptor superfamily and acts as a ligand-dependent transcription factor, playing key roles in maintenance of adipose tissue and in regulation of glucose and lipid homeostasis. This receptor is the target of thiazolidinediones, a class of antidiabetic drugs, which improve insulin sensitization and regulate glycemia in type 2 diabetes. Despite the beneficial effects of drugs, such as rosiglitazone and pioglitazone, their use is associated with several side effects, including weight gain, heart failure, and liver disease, since these drugs induce full activation of the receptor. By contrast, a promising activation-independent mechanism that involves the inhibition of cyclin-dependent kinase 5 (CDK5)-mediated PPARγ phosphorylation has been related to the insulin-sensitizing effects induced by these drugs. Thus, we aimed to identify novel PPARγ ligands that do not possess agonist properties by conducting a mini-trial with 80 compounds using the sequential steps of thermal shift assay, 8-anilino-1-naphthalenesulfonic acid fluorescence quenching, and a cell-based transactivation assay. We identified two non-agonist PPARγ ligands, AM-879 and P11, and one partial-agonist, R32. Using fluorescence anisotropy, we show that AM-879 does not dissociate the NCOR corepressor in vitro, and it has only a small effect on TRAP coactivator recruitment. In cells, AM-879 could not induce adipocyte differentiation or positively regulate the expression of genes associated with adipogenesis. In addition, AM-879 inhibited CDK5-mediated phosphorylation of PPARγ in vitro. Taken together, these findings supported an interaction between AM-879 and PPARγ; this interaction was identified by the analysis of the crystal structure of the PPARγ:AM-879 complex and evidenced by AM-879’s mechanism of action as a putative PPARγ non-agonist with antidiabetic properties. Moreover, we present an optimized assay pipeline capable of detecting ligands that physically bind to PPARγ but do not cause its activation as a new strategy to identify ligands for this nuclear receptor.